Effects of Covid-19 Infection on Some Pancreatic Functions in Diabetic Patients at Thi-Qar Province/Iraq - Hadi, Hamid S.; Enayah, Sabah H. (University of Thi-Qar Journal of Science, 2022)
People with diabetes mellitus (DM) represent a population group that is at high risk of developing a poor prognosis for COVID-19.Having diabetes can lead to serious illness, ICU stay, and death from COVID-19.The current study included 150 participants with diabetes, 100 of whom had COVID-19 (46 males, 54 females), and 50 had diabetes only (28 males and 22 females), aged between 37 and 69 years. The current situation is in the isolation center for people infected with the Corona virus at Al-Hussein Teaching Hospital and Shatrah General Hospital in Thi-Qar Governorate.The study included the impact of COVID-19 infection and its effect on pancreatic function.The results of the current study recorded a significant increase in fasting blood glucose concentration and cumulative glucose concentration in diabetic patients infected with Covid-19 virus compared to diabetic patients only by gender, the results also indicated an increase in fasting glucose and cumulative glucose levels in both male and female COVID patients compared to only diabetic patients. The concentration of pancreatic hormones also increased significantly in both male and female patients infected with Covid-19 virus compared to diabetic patients. According to age groups and BMI, cumulative and fasting glucose concentrations did not register a significant difference according to age groups, while according to BMI, cumulative and fasting glucose concentrations increased in patients with normal weight. Trypsin concentration increased significantly in the first age group, while glucagon increased in the second age group. Trypsin and glucagon did not score a significant difference according to BMI